Ace school

with brainly

  • Get help from millions of students
  • Learn from experts with step-by-step explanations
  • Level-up by helping others

A community for students.

Solve, using the substitution method. 4x + 2y = 11 x – 2 = – 2y

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Join Brainly to access

this expert answer

SIGN UP FOR FREE
Is \[2y=11-4x\] Right?
Multiply the second equation by 2
and then subtract it from the first

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

Ok, so \[2x-4=-4y?\]
Wait.. actually multiply the second equation by 4. That way you eliminate the x term
\[4x-8=-8y\]
How would I subtract it from the first equation? X becomes eliminated than what?
When x is eliminated, you can find the y term
substitution method. (not elimination method) 4x + 2y = 11 x – 2 = – 2y (find 'x' from here, by adding 2 on both sides)
Once you find the y term, you can substitute it in any of the above equations, and then you get x.
x=y?
So 6y=11?
@hartnn you'll still have the y term
x – 2 = – 2y x = 2-2y plug this in 1st equation 4(2-2y) +2y =11 simplify and get y
ask if you don't get that ^
@hartnn , but can't you solve it using elimination as well?
8-8y+2y=11
-10y=3?
the system can be solved by elimination method, but since the question specifically asks for substitution, we need to use substitution
-8y +2y = ... ?
6y
8-6y=11 -6y=3 y=-1/2
YES :)
now find x
Okkkkk :)
x=3
So its this bit.ly/1ewUix3
\(\huge \checkmark \)
(3,-1/2) Right?
yes, it is correct.
Thanks! Should I give the medal to potatoes or you? He tried... but you helped
i'm not here for medals. you understand thats my medal :)
:D
Also.. I'm a she :) And my method was wrong for this problem! Sorry!

Not the answer you are looking for?

Search for more explanations.

Ask your own question